Molecular identification of gelidioid algae (Gelidiales, Rhodophyta) from Singapore with a description of Gelidium sentosaense sp. nov. Issue 3 (1st March 2016) - Boo, Ga Hun; Cai, Yixiong; Boo, Sung Min
Abstract: Gelidioid specimens from Singapore were analyzed using sequences of cox 1 and rbc L to identify the species. Both datasets revealed the presence of four species: Gelidiella acerosa, Pterocladiella bartlettii, Pterocladiella caerulescens and Gelidium sentosaense sp. nov ., described here. Gelidium sentosaense formed small tufts up to 1 cm high and occurred in monospecific patches on cement beds at the outlet of drainpipes at intertidal areas. A morphological investigation of fresh specimens collected from Singapore revealed that G. sentosaense was similar to Gelidium pusillum, which is limited to North Atlantic coasts. However, it was distinguished by longitudinal striations present on the surface of branches and rhizines scattered in the inner cortex and medulla. Phylogenetic analyses of rbc L and cox 1 sequences revealed that G. sentosaense consistently formed a clade with Gelidium sp. from Oman and Gelidium pluma from Hawaii but it was distinct from previously described Gelidium species.